Wat, poeta orficki - Kuczyńska-Koschany, Katarzyna (Colloquia Litteraria, 2012)
Wat, an orphic poet The most important context for many 20th century references to the myth of Orpheus and Eurydice remained Rilke’s poem Orpheus. Eurydice. Hermes (among others, Jastrun, Herbert, Miłosz); the author of the article wonders whether Rilke was equally important for Aleksander Wat as the author of Wiersze somatyczne [Somatic poems] as well as Wiersz ostatni [A Final Poem]. A comparison of the first edition of Wiersze somatyczne (“New Culture”, 1957) with its first book publishing (also in 1957) inclines the author to pose a question, why is this first version much more dramatic, somehow more “orphic”: did Wat soften a book version of the poem due to personal reasons (a soften phase of the illness) or was it because of censorship’s intervension? Referring to Orpheus, the author also indicates significant painting contexts (Moreau, Delville, Redon) and sculpture contexts (Rodin); it becomes useful during Wat’s interpretation – his very pictorial illustration (e.g. in the poem Na wystawie Odilon Redona) is also “orphic”, full of blackness. Nevertheless, it seems that Wat’s orphic descent into blackness, inside oneself, into death is even more acute than Rilke’s – since Wat writes about himself, his own death and his own funeral (Wiersz ostatni).